2012
DOI: 10.1002/app.38166
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of TiO2 nanofibers via using polylactic acid as template

Abstract: A simple procedure is reported for the fabrication of TiO 2 nanofibers via electrospinning technique using polylactic acid (PLA), tetrabutyl titanate, and hexafluoroisopropanol as a spinning solution. TiO 2 nanofibers (600-700 nm in diameter), with bundled nanofibrils align in the fiber direction, are obtained from the calcination of the as-spun TiO 2 /PLA composite nanofibers at 550 C. The structure and physicochemical property of generated nanofibers are elucidated by Fourier transform-Infrared radiation spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…After that, a significant mass loss between 280–390 °C is observed, which corresponds to the decomposition of the PLA. Finally, from 390 °C to 500 °C thermal analysis curves slow down to complete the decomposition of the PLA matrix [33] until a constant mass is reached. The constant mass remaining at the end of each TGA experiment (see Figure 3 for PLA/TiO 2 -100 and Figure S2 for PLA/TiO 2 -21) corresponds to the inorganic material, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…After that, a significant mass loss between 280–390 °C is observed, which corresponds to the decomposition of the PLA. Finally, from 390 °C to 500 °C thermal analysis curves slow down to complete the decomposition of the PLA matrix [33] until a constant mass is reached. The constant mass remaining at the end of each TGA experiment (see Figure 3 for PLA/TiO 2 -100 and Figure S2 for PLA/TiO 2 -21) corresponds to the inorganic material, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[16]. Also, electrospinning has been successfully used for synthesis of TiO 2 nanofibers by using solutions that contained poly (vinyl pyrrolidone) (PVP) and Ti(IV)-isopropoxide [17,18], polyvinyl acetate (PVAc) and titanium tetraisopropoxide [19], polylactic acid (PLA), tetrabutyl titanate, and hexafluoroisopropanol [20]. The latter, PLA/TiO 2 (anatase) nanofibers, have also been tested for photocatalytic degradation of methyl orange with excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (b) depicted the spectrum of the PVP–ZnAc 2 composite nanofibers and it was seemed the same as Figure (a). This indicated that most of the ZnO precursor was embedded in the PVP chain . Moreover, the strong absorption peak of the carbonyl group stretching vibration was shifted to 1670 cm −1 in the PVP–ZnAc 2 composite nanofibers.…”
Section: Resultsmentioning
confidence: 90%